Comparison between Pelvic IMRT and 3D-CRT in Combination with Chemotherapy via Nrf2 Expression on the High-Risk Endometrial Cancer - Wang, Na; Zhang, Xia; Xu, Shuwen; Li, Xuehui; Meng, Yali; Dou, Zhixiang (Cellular and Molecular Biology, 2022)
This study aimed to explore the clinical efficacy of pelvic intensity-modulated radiation therapy (IMRT) and 3-dimensional conformal radiotherapy (3D-CRT) in combination with chemotherapy on high-risk endometrial cancer. The effect of these methods is evaluated via Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) expression, the levels of chitinase protein 40 (YKL-40), human epididymis protein 4 (HE4), and prolactin (PRL) in serum. For this purpose, between August 2014 and July 2017, 114 endometrial cancer patients admitted to this hospital for treatment were randomized into the observation group (n=60) and control group (n=54). Following the surgery, patients in these two groups received the chemotherapy of taxol and carboplatin (TC). Based on the chemotherapy, patients in the observation underwent the IMRT, while those in the control group adopted the 3D-CRT. The Nrf2 expression was performed based on the Real-time PCR technique. The incidence rate of adverse reactions was a 3-year recurrence rate and mortality rate. Results showed that after treatment, levels of YKL-40, HE4, and PRL in the serum of patients in two groups decreased compared to those before treatment (all P < 0.05). In comparison, the difference between the two groups showed no statistical significance (P > 0.05). The evaluation of Nrf2 transcription factor expression showed significant differences started in comparisons of the Nrf2 Expression between two groups (P > 0.05), and this enhancement was significant in the control group after treatment. Comparison of the incidence rates of the bone marrow suppression during treatment showed no significant difference (P > 0.05). However, the incidence rates of radiation enteritis and radio-cystitis in the observation group were much lower than those in the control group (P < 0.05). During the follow-up, there were five patients in the control group and 7 in the observation group losing to the follow-up, and among the remaining subjects, no significant difference was identified in the comparison of the recurrence rate or mortality rate between the two groups (all P > 0.05). In general, Pelvic IMRT in combination with chemotherapy is a promising and safe candidate for high-risk endometrial cancer with mild radiation injury; besides, YKL-40, HE4, and PRL are the effective indicator for the prediction of efficacy in chemotherapy for endometrial cancer.